PENGENALAN METODE INVESTIGASI DALAM PEMBELAJARAN MATEMATIKA PADA KONSEP PECAHANDI SDN 11 PEGUYANGAN DENPASAR - Susilawati, M. (Buletin Udayana Mengabdi; Vol 10 No 2 (2011): Volume 10 No.2 – September 2011, 2012)
The purpose of this activity is to improve the students’ understanding about the concept of fractions by applying investigation method. The topic is “to share with friends”. Compared the mean pre-test (53.4375) to the mean post-test (80.4375) indicated that the mean post-test is higher than the mean pre-test, it means that an improvement in the ability of students to solve the fractions questions after learning method of investigation . Similarly, the analysis results obtained using the t test is p value = 0.000 which is smaller than ? = 0.05, meaning that ho was rejected, it indicates that an improvement of students understanding about the concept of fractions.